Cyber Public Relations Strategy in Increasing Participation of the Certified Internship and Independent Study (MSIB) Program Through Instagram @magangmerdeka - Gunawan, Refa Zahra; Taufiqurrahman (Jogjakarta Communication Conference (JCC), 2025)
Universities in Indonesia must adapt to prepare graduates who meet the needs of the world of work in the era of the Industrial Revolution 4.0. The Merdeka Belajar Kampus Merdeka (MBKM) or Freedom to Learn-Independent Campus program initiated by the Directorate General of Higher Education in the Ministry of Education and Culture Indonesia has organized the Certified Internship and Independent Study (MSIB) Program which provides real learning experiences for students. The Marketing and Public Relations (MPR) of the program implements a Cyber Public Relations strategy through Instagram @magangmerdeka to disseminate information and interact with students. This study aims to describe the Cyber Public Relations strategy implemented by the MPR Department in increasing student participation in the MSIB batch 4, 5, and 6 program through Instagram. The method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews and document studies from the @magangmerdeka account. The results showed that the MPR Department implemented a Cyber Public Relations strategy based on Holtz's theory, namely strategic with the Feature, Advantage, Benefit approach; integrated using pillar content and Integrated Marketing Communication (IMC); targeted with a specific audience; and measurable through engagement rate, impression, conversion rate, and the AIDA model which emphasizes Awareness & Interest. Obstacles include the continuity of IMC messages and communication limitations due to the